Social groups: A theoretical–analytical sociological study (a revised study, adapted from a master’s thesis). - Qader, Pshtiwan Mahmoud Qader; Faraj, Prof.Dr. Najat Mohammad Faraj (Sulaimani Journal for Humanities, 2025)
This is a descriptive analytical study that discusses the analysis of the role of social values from the perspective of sociologists. This is because social values are a key subject in directing individual and collective behaviour, initially acquired within the family as the primary entity where the child learns the social values of society. After the family, other societal institutions such as schools, religious institutions (mosques and churches), peer groups, and media organizations take on this role, aiming to preserve the balance and health of social relations through these institutions. This research presents the views of sociologists regarding social values in relation to the actions and behaviours of individuals in social life, with the aim of clarifying and understanding the role of social values from the perspective of sociologists (Émile Durkheim, Max Weber, Talcott Parsons). These scholars generally believe that social values are a factor in the cohesion and preservation of the social system and the interaction between individuals, and are instrumental in transmitting social values from one generation to another. The study also concluded that individuals acquire social values through social institutions, which become a basis for building the individual's personality in society.
Keywords: Social values; sociological scientists; social relations; social institutions; social behavior